Accessing science museum exhibits with interactive signing dictionaries. Issue 3 (2nd October 2017) - Vesel, Judy; Robillard, Tara
Abstract: Evidence suggests that content incorporated into science museum exhibits remains out of reach for many visitors who are deaf or hard of hearing and who communicate in sign language. The implementation research described in this article was conducted by TERC, Inc. at the Museum of Science (MoS), Boston. The purpose was to examine use of a mobile Signing Science Dictionary, Signing Science Pictionary, and Signing Math Dictionary to help this population access the American Sign Language (ASL) vocabulary required for interacting with science museum exhibits. The study consisted of 11 families and 52 participants – 24 adults and 28 children. Of these, 12 children and one adult were deaf. The mixed methods research design incorporated a four-step protocol that involved (a) collecting pre-visit information, (b) observing families using the dictionaries, (c) conducting an exit interview, (d) a follow-up survey. Results suggest that the visual features available in the dictionaries make them valuable learning tools for deaf and hard of hearing science museum visitors, effectively providing users with access to exhibit content. However, further research is needed to study the dictionaries' impact in more exhibits at the MoS and other museum venues.